PENGARUH ADVERTISING DAN PUBLIC RELATION DALAM MEMBANGUN CITRA MEREK: STUDI KASUS PADA PRODUK FASHION RUCAS - Azizatul Fitriah; Dini Khumrotin; Candra Dwi Saputra; Meigi Tidarsari (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine how advertising and public relations (PR) influence the brand image of RUCAS fashion products. With the increasingly competitive fashion industry, which contributes over 17% to the creative economy's GDP, understanding effective communication is crucial. Using explanatory research methods and a quantitative approach, data were collected through an online questionnaire distributed to 107 individuals, primarily young people active on social media. Multiple linear regression was used to analyze the data to assess the causal relationship between the variables. The results indicate that advertising and PR together have a strong influence on brand image, building trust and emotional connections among consumers, particularly among young people. The novelty of this study lies in the integration of digital marketing communication tactics that link advertising and public relations within the local fashion industry, a relatively under-researched area. The findings are significant, particularly for education, as they can serve as a guide for developing more tailored marketing communication curricula. These findings are expected to provide useful guidance for local fashion brands to improve their communication and strengthen their position in an increasingly competitive market. Thus, this research not only helps in developing marketing communication theory, but also provides practical guidance for implementing it.